Assisting primary school children to progress through the van hiele's levels of geometry thinking using google sketchup - Tan, Tong Hock, 1969-; Mohd. Salleh Abu, supervisor; Fakulti Pendidikan (2011)
Thesis (Sarjana Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2011